Students' Contribution as Agents of Change in Building National Resilience Amidst Global Challenges - Kori Hana Putri; Naura Ervin Kusuma Tri Oktavia (Annujum: Journal of Humaniora and Law, 2025)
Maintaining the integrity of the Unitary State of the Republic of Indonesia requires strong national resilience, especially in the face of globalization and multifaceted global challenges. Educated students serve as key agents of transformation, contributing significantly to bolstering this resilience. This research explores the connection between students' roles and the efficacy of national resilience by reviewing pertinent journal literature. Employing a qualitative method, it reviews 12 selected articles out of 20 journals, extracting information on student involvement and national resilience, followed by thematic analysis of the study outcomes. Findings reveal that diminished student input in specific areas stems from a pragmatic academic environment and insufficient collaboration between youth groups and governmental strategies. This situation worsens due to global cultural impacts that undermine national pride and inadequate hands-on civic training. Additionally, initiatives to enhance national resilience encounter barriers from digital upheavals and ideological divides. Ultimately, the success of national resilience heavily relies on the extent of active student engagement. Thus, it is crucial to implement more structured adaptive national defense education programs.